Isolation and Molecular Identification of Rhizospheric Fungi Associated with Opuntia cochenillifera from Semiarid in Alagoas, Brazil - João Manoel, da Silva; Araujo Dalbon, Viviane; la Rosa Massahud, Regla Toujaguez; Molina Acevedo, Juan Pablo; Machado de Medeiros Ferro, Mayra; Carvalho dos Santos, Tania Marta; Simões do Amaral Alves, Elizabeth; Andrade Lima, Gaus Silvestre (International Journal Of Agriculture & Biology, 2024)
The aim of this study was isolation and identification of rhizospheric fungi in association with cacti [Opuntia cochenillifera (Linnaeus) Miller] in an area under salinization and desertification, as well as to model their chemical and mineralogical attributes. The experimental area was located in the municipality of Ouro Branco-AL, Brazil. To determine the microbial population, rhizospheric soil was collected from a depth of 0–20 cm. The dilution was carried out to fractions 10-3, 10-4 and 10-5 and inoculated in Petri dishes containing selective culture media. A count of colony forming units (CFU), and morphological identification was performed. The isolates were subjected to DNA extraction, followed by amplification through PCR. The sequences were analyzed with Staden Package and MEGA softwares, followed by the BLASTn search in GenBank. Through the phylogenetic analysis of the rDNA ITS, the species belonging to Coprinellus, Paecilomyces, Aspergillus, Penicillium, and Neurospora were identified. These genera are in the literature for their metabolic richness, being applicable to biotechnological processes for growth promotion in plants, as well as other processes of industrial interest. © 2022 Friends Science Publishers